Peningkatan Kesadaran Hukum Masyarakat Melalui Sosialisasi KUHP Nasional di Desa Waisarisa - Jusuf Leiwakabessy; Michael R. Singkery; Riski Putri Nurani; Risda Ilyas; Deo Augusti Luhulima; Dylen Vanky Neite; Ravelito Tasidjawa; Sahrini Dwi Aisyah (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
This community service activity aims to improve the community’s legal understanding and awareness through outreach on the National Criminal Code (KUHP) in Waisarisa Village, West Kairatu Subdistrict, West Seram Regency. The issues identified include the community’s limited understanding of the provisions of the New Criminal Code and a lack of legal awareness in daily life. The method used in this activity was a quantitative descriptive approach with a one-group pre-test and post-test design. Data collection was conducted through pre-tests, post-tests, and observations of 46 respondents who participated in the dissemination activity. The results of the activity showed an increase in the community’s legal understanding and awareness after participating in the outreach. The average pre-test score of 68.48% increased to 100% on the post-test, representing a 46.03% increase. The most significant improvement occurred in the indicators of understanding of the new Criminal Code and community legal awareness, each of which increased by 96%. These results indicate that legal outreach activities using an educational and participatory approach are effective in improving the community’s legal literacy. It is hoped that this initiative will foster a culture of legal awareness and enhance the community’s compliance with legal regulations in social life.